Assessment and management of the geomorphological heritage of Monte Pindo (NW Spain): a landscape as a symbol of identity - Casais, Manuela Costa (2015)
This study focuses on the granite mountain known as Monte Pindo (627 m above sea level) in the Autonomous Community of Galicia (NW Spain). This territory is included in the area classified as “Costa da Morte” in the “Politica de Ordenación Litoral” (POL) (Coastal Planning Policy) for the region of Galicia. This coastal unit, located between “Rías Baixas” and “Cape Fisterra” has great potential for demonstrating geological processes and its geomorphological heritage is characterized by a high degree of geodiversity of granite landforms. The main objective of our work is to assess the geomorphological heritage of the site, thus revealing its wide geodiversity. We shall analyze and highlight: its scientific value, developing an inventory of granite landforms; its educational valuel and its geotouristic potential. It must be ensured that the Administration understands that natural diversity is composed of both geodiversity and biodiversity. Only then will the sustainable management of Monte Pindo become possible by integrating natural and cultural heritage values. The goal is to ensure that Monte Pindo and its immediate surroundings become a geopark with the aim of promoting local development projects based on the conservation and valorization of its geological heritage.